Evaluasi Mutu Fisik Tablet Antalgin Dengan Bahan Penghancur Amilum Kulit Pisang (Musa paradisiacal) Metode Granulasi Basah - Sri Saptuti Wahyuningsih; Siwi Hastuti (Jurnal Farmasi Indonesia, 2017)
Tablets are solid preparations taken by oral. Some people consider banana peel as a waste, whereas banana peel contains amylum which can be used as additional material. This study aims to determine the ability of banana peel as a crushing material and its effect on the physical character of antalgin tablets.This research was done by making the formula using variation of banana peel concentration (5%, 10%, 15%). The research begins with granule preparation with wet granulation method, then continued compressing of tablets. Tests include physical character of granules and physical character of antalgin tablets (uniformity of size and weight, hardness, distegration test, friability) for each formula.The results showed that the difference in thickness of the tablets due to differences in pressure at the time of printing, granule quality and the number of fines on the granule. Uniformity of weight is affected granule quality including granule flow character. The increasing concentration of disintegrant causes the tablet to have a decreasing hardness and decay time, while the friability of the tablet increases. The result of ANOVA test shows that there is a significant influence between the variation of disintegrant concentration on the physical character of antalgin tablets. Conclusion. Banana peel can be used as an antalgin tablet crusher. The increased variation of banana peel concentration as a disintegrant resulted in decreased hardness and disintegration time of tablets as well as an increase in tablet friability